1989
DOI: 10.1111/j.1600-051x.1989.tb01621.x
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid burnishing of dentinal root surfaces

Abstract: The integrity of formalin-fixed periodontally diseased root surfaces was assessed following root planing to dentin and citric acid application. Extracted human teeth (fixed in 10% formalin), with crowns removed, were vertically sectioned in half. A horizontal groove on each proximal surface marked the extent of attachment loss. The diseased root surface was vigorously root planed to expose dentin. Cotton pellets, soaked in a saturated solution of citric acid, were either "placed" (control) or "burnished" (vigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 42 publications
2
31
2
Order By: Relevance
“…3). These results are in agreement with those of previous studies (17,18), which described considerable changes in surface morphology after burnishing with citric acid.…”
Section: Discussionsupporting
confidence: 94%
“…3). These results are in agreement with those of previous studies (17,18), which described considerable changes in surface morphology after burnishing with citric acid.…”
Section: Discussionsupporting
confidence: 94%
“…3 and 6). A similar pattern of deeply tufted collagen fibrils has been observed to result from citric-acid burnishing of a root surface as part of a tissue-regenerative periodontal treatment (Sterrett and Murphy, 1989). The physical rubbing action combined with the chemical action of citric acid was found to enhance the removal of chemically dissolved inorganic dentin material and surface debris, exposing a deeply tufted collagen fibril surface topography, similar to the appearance of a "shag carpet".…”
Section: Discussionmentioning
confidence: 89%
“…[7] Sterrett and Murphy and Trombelli et al have also demonstrated similar findings. [18,28] After conditioning with respective solutions, the specimens were then processed and examined under SEM at ×1500 magnification to evaluate: Efficacy in removal of smear layer, total number of dentinal tubules present per specimen, number of patent dentinal tubules and their diameter.…”
Section: Discussionmentioning
confidence: 99%